Critical Review: The Impact of Political Prisons on Political Participation (The Case of Egypt’s Muslim Brotherhood) - Khattab, Fatma (International Studies. Interdisciplinary Political and Cultural Journal, 2024)
Many revolutionary figures throughout history proved their corrupted intention whenever they reached authority (e.g., the Iranian revolution, Burma’s Aung Suu Kyi). Some political leaders in Egypt claim they own it all depending on whom they represented in the latest major social uprising, and they define what is moral or who shall be the target for future political manoeuvres of the ruling military regime. With no one taking the lead for democratising the system, and the ex-minister of defence, incumbent President Abdelfattah Al-Sisi allegedly caught up in an internal fight with a corrupt government, the country’s better future seems to be a long and arduous struggle away. This paper addresses the overlapping and misleading media and political utterances of Egyptian opposition, who either takes a popular stand or loses followers through democratisation itself.